Dynamics of Attitude Change and Creative Writing Ability of Santri Mutawassith Through Mentoring Based on the Book Husnul Isgho’ Fi Darsil Insya’ - Muhammad Taufiq (Universitas Islam Internasional Darullughah Wadda'wah, 2026)
This applied community service program examined attitude changes and creative Arabic writing ability (maharah kitabah) among twenty santri mutawassith at Pondok Pesantren Dalwa, East Java, who participated in a twenty-day intensive mentoring program based on the book Husnul Isgho' fi Darsil Insya'. Despite foundational Nahwu knowledge, students initially struggled with imla' accuracy, limited vocabulary, and complex sentences. Program evaluation through interviews, observations, portfolios, and field notes revealed a significant positive attitude shift: from 70% viewing writing as difficult or boring to 85% feeling confident and 75% finding writing easier and more enjoyable post-program. Writing improvement occurred in three progressive phases: mastering imla' and basic sentences, developing paragraphs with varied rhetorical styles (uslub qashr, ithnab, musawah), and independent creative writing with peer correction. Supporting factors included the book's eclectic method, modern vocabulary, personal mentoring, and the Arabic-speaking pesantren environment. Constraints were Arabic instructions and limited time. The program concludes that intensive book-based mentoring accelerates both technical writing skills and self-efficacy, recommending a sustainable writing club and peer-tutor training.